Feasibility and Tolerance of Fingertip Peripheral Arterial Tonometry Measurements in School-Aged Children - Karolien Van De Maele; Karolien Van De Maele; Karolien Van De Maele; Roland Devlieger; Roland Devlieger; Steven Provyn; Jean De Schepper; Inge Gies; Inge Gies (Frontiers Media S.A., 2021)
Background: Assessment of the endothelial function of the microvasculature by peripheral arterial tonometry (PAT) has gained increasing popularity in pediatrics. Discomfort or experienced pain during fingertip PAT has only been studied in adolescents and adults.Methods: In 142 children (aged 4-11 years old), a fingertip PAT with a commercial device (EndoPAT 2000®) as well as a caliper and ultrasound examination of peripheral skinfolds were performed as part of a cross-sectional cohort study. In 110 children, Faces Pain Scale (FPS-R) data were collected after PAT and skinfold measurements by caliper and ultrasound.Results: In 111 out of the 142 PAT measurements (78.2%), a reactive hyperemia index (RHI) could be obtained. The most frequent error messages by the software was a "too noisy" and/or a "poor quality" signal. The success rate was higher in children aged older than 6 years (83.1 vs. 44.4%; p < 0.001). Median (range) FPS-R after PAT was 0 (range 0-6) but was significantly higher than the median pain experienced after caliper measurements of peripheral skinfolds (p < 0.001). No pain was experienced by 59 of the 110 children (54.1%).Conclusion: PAT testing is feasible in the great majority of school-aged children, and the procedure is well-tolerated.